A lightweight secure authentication for vehicular ad-hoc networks by message encapsulation and trusted authority dependency-less scheme / Tarak Nandy - Tarak , Nandy (2022)
A vehicular network is a collection of vehicles and other components that are facilitated with versatile sensors to communicate, which are also backed by authentication mechanisms. Present authentication protocols for vehicular networks have a focus on either the lightweight feature or the security feature. However, privacy during authentication is neglected by many researchers. Existing schemes depend on a trusted authority to check the legitimacy of a communicating node. These existing schemes suffer from the infrastructure-less scenario and rely on a secure communication channel during the registration phase, which may not always be available. Two novel authentication protocols are designed in this thesis to address these concerns. Firstly, an elliptic curve cryptography-based (ECC) authentication scheme is proposed. A secure key establishment is shown, and Pseudo-id-based authentication is used to provide privacy preservation on the scheme. Symmetric-key cryptography with a session key is used for message encryption during communication. Secondly, an enhanced lightweight and secure authentication protocol (ELSAP) for V2V Communication in VANETs is proposed. The scheme is equipped with self-authentication before communication that is able to enhance network feasibility. This proposed method, in return, needs less message transfer during authentication as well as communication. Therefore, it contributes to the lightweight features of the proposed scheme. The experimental analysis shows that the proposed methods outperformed existing related authentication schemes. Furthermore, the simulation results reflect the practicality of the projected scheme. To conclude, the proposed proposal creates effective communication with other network devices and ensures security and privacy.